Alteration of a single serine in the basic domain of the Epstein-Barr virus ZEBRA protein separates its functions of transcriptional activation and disruption of latency. - Francis, A L (1997)
The ZEBRA protein from Epstein-Barr virus (EBV) activates a switch from the latent to the lytic expression program of the virus. ZEBRA, a member of the bZIP family of DNA-binding proteins, is a transcriptional activator capable of inducing expression from viral lytic cycle promoters. It had previously been thought that ZEBRA's capacity to disrupt EBV latency resided primarily in its ability to activate transcription of genes that encode products required for lytic replication. We generated a point mutant of ZEBRA, Z(S186A), that was not impaired in its ability to activate transcription; however, this mutation abolished its ability to initiate the viral lytic cascade. The mutant, containing a serine-to-alanine substitution in the DNA-binding domain of the protein, bound to several known ZEBRA-binding sites and activated transcription from reporters bearing known ZEBRA-responsive promoters but did not disrupt latency in EBV-infected cell lines. Therefore, initiation of the EBV lytic cycle by the ZEBRA protein requires a function in addition to transcriptional activation; a change of serine 186 to alanine in the DNA-binding domain of ZEBRA abolished this additional function and uncovered a new role for the ZEBRA protein in disruption of EBV latency. The additional function that is required for initiation of the lytic viral life cycle is likely to require phosphorylation of serine 186 of the ZEBRA protein, which may influence either DNA recognition or transcriptional activation of lytic viral promoters in a chromatinized viral episome.